2006
DOI: 10.1111/j.1365-2893.2006.00791.x
|View full text |Cite
|
Sign up to set email alerts
|

Liver‐related mortality in human‐immunodeficiency‐virus‐infected patients between 1995 and 2003 in the French GERMIVIC Joint Study Group Network (MORTAVIC 2003 Study)*

Abstract: The objective of the present study was to determine mortality because of end-stage liver disease (ESLD) in a nationwide population of HIV-infected patients, 7 years following the introduction of highly active antiretroviral therapy (HAART). All departments of internal medicine and infectious diseases from the GERMIVIC Study Group prospectively recorded all deaths in HIV-infected patients during 2003. Fifty-nine departments, following a total of 20 940 HIV-infected patients, participated in the study. Results w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
89
0
5

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(96 citation statements)
references
References 26 publications
2
89
0
5
Order By: Relevance
“…However, this has also meant that the causes of death have shifted to predominantly non AIDS-related diseases, with a high proportion of end-stage liver diseases being observed (2,(7)(8)(9)(10). These major hepatic complications have emerged in the context of excessive alcohol use -metabolic issues such as steatosis (11) and portal hypertension (12) may also be related to antiretroviral treatment toxicity but their role in liver mortality remains to be defined.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this has also meant that the causes of death have shifted to predominantly non AIDS-related diseases, with a high proportion of end-stage liver diseases being observed (2,(7)(8)(9)(10). These major hepatic complications have emerged in the context of excessive alcohol use -metabolic issues such as steatosis (11) and portal hypertension (12) may also be related to antiretroviral treatment toxicity but their role in liver mortality remains to be defined.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies including the French national survey, "Mortalité 2000", have shown that complications of HCV and HBV are the second most frequent underlying cause of death after AIDS in HIV-infected patients, accounting for around 10% of deaths (1)(2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Co-infection s associated with a higher mortality than mono infection with either virus alone [46]. This liver-related mortality decreased following introduction of HAART (highly active antiretroviral therapy) [47]. Studies have shown that excessive consumption of alcohol appears to be a cofactor that increases mortality from liver disease in co-infected patients [40,47].…”
Section: Route Of Transmissionmentioning
confidence: 99%
“…This liver-related mortality decreased following introduction of HAART (highly active antiretroviral therapy) [47]. Studies have shown that excessive consumption of alcohol appears to be a cofactor that increases mortality from liver disease in co-infected patients [40,47]. Most cases of liver associated mortality in co-infected patients are due to end-stage liver disease or hepato-cellular carcinomia [48].…”
Section: Route Of Transmissionmentioning
confidence: 99%